Budaya Kesehatan Pemulung di TPA Regional SARBAGITA Kelurahan Pedungan Kecamatan Denpasar Selatan Kota Denpasar - Ni Luh Kristina Megayanti; I Wayan Suwena; Ni Made Wiasti (Department of Anthropology Udayana University, 2023)
Research on the Health Culture of Scavengers at the SARBAGITA Regional TPA, began with cases of skin diseases that mostly suffered by scavengers as a result of their work to find junk items in waste. This study tries to examine the health culture of scavengers in their daily lives. The main problem in this research is focused on the health behavior of scavengers at the SARBAGITA Regional TPA. This study uses the theory of health behavior popularized by Dunn. The method used is a qualitative research method using data collection techniques through observation, interviews, and literature study. The analysis used in this research is interpretive descriptive. Where this study shows that the health culture of the scavengers at the SARBAGITA Regional TPA is part of their health behavior, which results in preventive and promotive behavior of scavengers in maintaining and improving their health. There is also a caring and apathetic behavior of scavengers in responding to the health problems they suffer.